Deficits in Auditory Rhythm Perception in Children With Auditory Processing Disorder Are Unrelated to Attention - Sidiras, Christos; Iliadou, Vasiliki Vivian; Nimatoudis, Ioannis; Grube, Manon; Griffiths, Tim; Bamiou, Doris-Eva (Frontiers in Neuroscience, 2019)
Auditory processing disorder (APD) is defined as a specific deficit in the processing of audi-tory information along the central auditory nervous system, including bottom-up and top-down neural connectivity. Even though music comprises a big part of audition, testing music perception in APD population has not yet gained wide attention in research. This work tests the hypothesis that deficits in rhythm perception occur in a group of subjects with APD. The primary focus of this study is to measure perception of a simple auditory rhythm, i.e. short isochronous sequences of beats, in APD children and to compare their performance to age-matched normal controls. The secondary question is to study the relationship between cognition and auditory processing of rhythm perception. We tested 39 APD children and 25 control children aged between 6 and 12 years via a) clinical APD tests, including a monaural speech in noise test, b) Isochrony task, a test measuring the detection of small deviations from perfect isochrony in a isochronous beats sequence, and c) two cognitive tests (audi-tory memory and auditory attention). APD children scored worse in Isochrony task compared to the age-matched control group. In the APD group, neither measure of cognition (attention nor memory) correlated with performance in Isochrony task. Left (but not right) speech in noise performance cor-related with performance in Isochrony task. In the control group a large correlation (r=-.701, p=.001) was observed between Isochrony task and attention, but not with memory. The results demonstrate a deficit in the perception of regularly timed sequences in APD that is relevant to the perception of speech in noise, a ubiquitous complaint in this condition. Our results suggest a) the existence of a non-attention related rhythm perception deficit in APD children and b) differential effects of attention on task performance in normal vs. APD children. The potential beneficial use of music/rhythm trai-ning for rehabilitation purposes in APD children would need to be explored.